Such a bad influence - Muenter, Olivia (Quirk Books, 2024)
"Hazel Davis is drifting: she’s stalled in her career, living in a city she hates, and less successful than her younger sister @evelyn, a lifestyle influencer. Evie came of age on the family YouTube channel after a viral video when she was five. Ten years older and spotlight-averse, Hazel managed to dodge the family business—so although she can barely afford her apartment, at least she made her own way. Evie is eighteen now, with a multimillion-dollar career, but Hazel is still protective of her little sister and skeptical of the way everyone seems to want a piece of her: Evie’s followers, her YouTuber boyfriend and influencer frenemies, and their opportunistic mother. So when Evie disappears one day during an unsettling live stream that cuts out midsentence, Hazel is horrified to have her worst instincts proven right. As theories about Evie’s disappearance tear through the internet, inspiring hashtags, Reddit threads, and podcast episodes, Hazel throws herself into the darkest parts of her sister’s world to untangle the truth. After all, Hazel knows Evie better than anyone else . . . doesn’t she?"